2013
DOI: 10.1103/physrevlett.110.136403
|View full text |Cite
|
Sign up to set email alerts
|

Global Structural Optimization of Tungsten Borides

Abstract: Tungsten borides are among a distinct class of transition-metal light-element compounds with superior mechanical properties that rival those of traditional superhard materials. An in-depth understanding of these compounds, however, has been impeded by uncertainties regarding their complex crystal structures. Here, we examine a wide range of chemical compositions of tungsten borides using a recently developed global structural optimization approach. We establish thermodynamically stable structures and identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
174
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(190 citation statements)
references
References 46 publications
14
174
1
1
Order By: Relevance
“…[20][21][22][23][24][25][26] Zhang et al [24] reopened the question on the correct crystal structure of WB 4 or WB 3 , as the calculated indentation hardness of WB 4 is lower than that of ReB 2 in contrast to the experimental result and the calculated normalized c/a ratio of WB 3 exhibits a negative pressure dependence, inconsistent with the observed trend. Li et al [25] in their latest study presented new thermodynamically stable structures for WB 3 (R 3m-''6u'') and WB 4 (P6 3 /mmc-''2u''). However, the DFT stability calculations so far never considered nonstoichiometric W 1Àx B 3 with defects in metal atom sites.…”
Section: Introductioncontrasting
confidence: 43%
See 2 more Smart Citations
“…[20][21][22][23][24][25][26] Zhang et al [24] reopened the question on the correct crystal structure of WB 4 or WB 3 , as the calculated indentation hardness of WB 4 is lower than that of ReB 2 in contrast to the experimental result and the calculated normalized c/a ratio of WB 3 exhibits a negative pressure dependence, inconsistent with the observed trend. Li et al [25] in their latest study presented new thermodynamically stable structures for WB 3 (R 3m-''6u'') and WB 4 (P6 3 /mmc-''2u''). However, the DFT stability calculations so far never considered nonstoichiometric W 1Àx B 3 with defects in metal atom sites.…”
Section: Introductioncontrasting
confidence: 43%
“…However, more recent theoretical calculations of band structure and physical properties (density functional theory calculations DFT) of this compound have inferred some confusion on the true crystal structure of ''WB 4 ''. [20][21][22][23][24][25][26] Whereas the first studies by Chretien and Helgorsky [15] reported a tetragonal unit cell for ''WB 4 '' (a = 0.634 nm, c = 0.450 nm), Rudy et al [16] claimed a hexagonal cell (a = 0.3004 nm, c = 0.3174 nm) but proposed ''WB 12 '' as a more appropriate composition. A first structure model was derived by Romans and Krug [17] from x-ray powder data backed by single crystal Laue and precession photographs indexed on a hexagonal lattice (a = 0.5200 nm, c = 0.6340 nm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For group VI, B0 of CrB2-x is close to constant for x < 0.167 after which it start to decrease whereas B0 of both MoB2-x and WB2-x decreases at small x, compared to x = 0, followed by a small increase up to x = 0.25 and 0.333, respectively, and then decreases at higher x. Recently, phonon calculations of WB2, with AlB2 structure, showed imaginary frequencies which indicates that it is dynamically unstable [41]. By modifying WB2, either through creation of puckered B-layers (R3 ̅ m or P63/mmc) or formation of B-vacancies, the imaginary frequencies are expected to disappear as well as stabilize the phase.…”
Section: (A) the Bulk Modulus B0 Of Mb2-x Is Shown As Function Of B-vmentioning
confidence: 99%
“…CALYPSO has been used to investigate a great variety of materials at high pressures [33][34][35][36][37][38]. Detailed information on the calculations is provided in the Supplemental Material [39].…”
mentioning
confidence: 99%